Q Fever Risk in Patients Treated with Chronic Antitumor Necrosis Factor-Alpha Therapy - Julianna Hirsch; Anna Astrahan; Majed Odeh; Nizar Elias; Itzhak Rosner; Doron Rimar; Lisa Kaly; Michael Rozenbaum; Nina Boulman; Gleb Slobodin (Case Reports in Infectious Diseases)
Q fever is a zoonotic bacterial disease caused by Coxiella burnetii. Tumor necrosis factor-alpha (TNF-α) plays a pivotal role in the defense against infection with this Gram-negative coccobacillus. Theoretically, patients who are treated with anti-TNF-α medications are at risk for developing chronic Q fever. We present two patients who developed Q fever while being treated with anti-TNF-α agents and discuss the significance of timely diagnosis of C. burnetii infection in these patients.